Agouti-related protein as the glucose signaling sensor in the central melanocortin circuits in regulating fish food intake - Han, Juan; Liang, Xiaofang; Guo, Yanzhi; Wu, Xiaoliang; Li, Ziqi; Hong, Tiannuo (Frontiers in Endocrinology, 2022)
Agouti-related protein (AgRP) is a neuropeptide synthesized by AgRP/NPY neurons and transcribed as 132 amino acids in humans and 142 amino acids (AgRP1) in Japanese seabass (Lateolabrax maculatus) fish. AgRP neurons are activated by hormonal signals of energy deficits and inhibited by signals of energy surpluses and have been demonstrated to have the ability to sense the dynamics of blood glucose concentrations as the “glucose sensor” in mammals. It is widely recognized that AgRP is an endogenous antagonist of the melanocortin-3 and -4 receptors (MC3R and MC4R) in the hypothalamus, exhibiting potent orexigenic activity and control of energy homeostasis. Most fish, especially carnivorous fish, cannot make efficient use of carbohydrates. When carbohydrates like corn or wheat bran are added as energy sources, they often cause feeding inhibition and metabolic diseases. When fishmeal is replaced by plant protein, this does not completely eliminate carbs, limiting the utilization of carbohydrates and plant proteins in aquaculture. Our previous study showed that AgRP, and not neuropeptide Y (NPY) is the principal protein molecule that correlates well with feeding behavior in Japanese seabass from anorexia to adaptation. The Ghrelin/Leptin-mTOR-S6K1-NPY/AgRP/POMC feed intake regulatory pathway responds to the plant-oriented protein which contains glucose. However, its regulatory function and mechanism are still not clear. This review offers an integrative overview of how glucose signals converge on a molecular level in AgRP neurons of the arcuate nucleus of the hypothalamus. This is in order to control fish food intake and energy homeostasis.